Detection of the Murine Double Minute2 (MDM2) gen in formalin-fixed tissue samples using PCR - Sanita, Hanifah Velda; Sayekti, Fitria Diniah Janah (Media Penelitian dan Pengembangan Kesehatan, 2026)
Background: Tissue preservation is a crucial procedure in pathological studies to maintain cellular and structural integrity, commonly performed through formalin fixation. However, formalin fixation may cause DNA degradation, posing challenges for molecular analysis. Detection of cancer biomarker genes, such as Murine Double Minute 2 (MDM2), can be performed using Polymerase Chain Reaction (PCR), a technique for amplifying specific DNA fragments. Objective: This study aimed to determine the presence of the MDM2 gene in formalin-preserved tissues stored for different periods using PCR. Methods: A descriptive qualitative design with random sampling was employed. The study was conducted at the Anatomical Pathology and Molecular Biology Laboratories of Sekolah Tinggi Ilmu Kesehatan Nasional. Samples included 10 hair and nail tissues as controls, and formalin-fixed tissues stored for 2 days, 1 month, 2 months, and 8 years. DNA isolation was performed using the Geneaid gSYNC™ DNA Extraction Kit. DNA quality was assessed by 1.5% agarose gel electrophoresis, while concentration and purity were measured using a UV-Vis spectrophotometer. DNA concentrations ranged from 320–420 ng/µL, with purity ratios between 0.8 and 1.125. Results: The results showed that the MDM2 gene (178 bp amplicon) was detectable in tissues stored for up to 2 months but was not detected in tissues stored for 8 years. Conclusion: These findings indicate that storage duration affects the success of gene detection in formalin-fixed tissues.